2022
DOI: 10.1186/s12913-022-08570-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of early essential newborn care implementation in four counties of western China

Abstract: Background Neonatal survival is a public health concern globally. However, the regional disparity in neonatal mortality between rural counties of western China and urban areas of eastern provinces remains high. Early essential newborn care (EENC), recommended by World Health Organization, refers to a set of cost-effective interventions to improve neonatal health and development outcomes. In this study, we aimed to explore the effectiveness of EENC implementation in four counties of western Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Most of the studies covered the care between birth and discharge or birth to 72 hours,14 18–20 23 26 27 30 33–35 41 43 46 49 51–58 61 62 64 67 69–73 76 78–80 82–85 four studies reported on follow-up care at home,16 47 48 50 one on care during ground ambulance transport37 and five studies covered end-of-life care 25 36 42 72 84. We found no studies that reported on home birth.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Most of the studies covered the care between birth and discharge or birth to 72 hours,14 18–20 23 26 27 30 33–35 41 43 46 49 51–58 61 62 64 67 69–73 76 78–80 82–85 four studies reported on follow-up care at home,16 47 48 50 one on care during ground ambulance transport37 and five studies covered end-of-life care 25 36 42 72 84. We found no studies that reported on home birth.…”
Section: Resultsmentioning
confidence: 89%
“…Satisfaction with care was covered in 25 studies,14–17 27 38 43 45 48 55 71–85 but only 15 had it as primary aim,14 15 38 43 45 55 72 74–77 79 81–83 with seven focused on overall satisfaction and the remaining focused on the care received during stay in neonatal intensive care unit (NICU) or on other specific aspects such as rooming-in, infrastructure, education at discharge, the administration of routine interventions or home-based care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey conducted in Cambodia and Lao PDR showed that the rates of EENC practice 15 min after birth were low (Kitamura et al 2022). The practice of skin-to-skin contact was not successfully introduced in China (Wang et al 2022). In addition, the executive criteria in some hospitals have not strictly corresponded to the EENC guidelines (Peven et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The practice of skin‐to‐skin contact was not successfully introduced in China (Wang et al. 2022). In addition, the executive criteria in some hospitals have not strictly corresponded to the EENC guidelines (Peven et al.…”
Section: Introductionmentioning
confidence: 99%